Co-crystal structure of a dinuclear (Zn-Y) and a trinuclear (Zn-Y-Zn) complexes derived from a Schiff base ligand - Sarr, Mamour; Diop, Mayoro; Thiam, Ibrahima Elhadj; Gaye, Mohamed; Barry, Aliou Hamady; Alvarez, Natalia; Ellena, Javier (European Journal of Chemistry, 2018)
The present investigation describes the synthesis and structural study of a metal-zinc ligand [ZnL.H2O], which was used to generate three dimensional supramolecular complex formulated as [Y{Zn(L)(SCN)}(SCN)2].[Y{Zn(L)(SCN)}2(DMF)2].(NO3). The title compound crystallizes in the triclinic space group P-1 with the following unit cell parameters: a = 14.8987(7) Å, b = 15.6725(8) Å, c = 19.2339(10) Å, a = 94.610(4)°, β = 103.857(4)°, γ = 101.473(4)°, V = 4234.4(4) Å3, Z = 2, R1 = 0.063 and wR2 = 0.96. For this compound, the structure reveals that one heterodinuclear unit [Y{Zn(L)(SCN)}(SCN)2] is co-crystallized with a heterotrinuclear unit [Y{Zn(L)(SCN)}2(DMF)2].(NO3). In the dinuclear moiety, the organic molecule acts as a hexadentate ligand and in the trinuclear unit, it acts as a pentadentate ligand with one of the oxygen methoxy group remaining uncoordinated. In both units the coordination environment of the zinc metal can be described as distorted square pyramidal. In the dinuclear unit the Y(III) is hexacoordinated while it is octacoordinated in the trinuclear unit. The environment of the Y(III) can be described as a distorted octahedral geometry in the dinuclear and as a distorted square antiprism in the trinuclear units respectively.